HOW MUCH DOES IT COST TO BE HAPPY? ON IMPERATIVE MECHANISMS AND PROGRAMS OF CONSUMPTION OF BEING IN NEOLIBERAL SOCIETY: How much does it cost to be happy? On imperative mechanisms and programs of consumption of being in neoliberal society - Caetano, Carla; Brandão, Leonardo (Revista Desenvolvimento Social, 2022)
In this article we review and analyze the book “Authentic Happiness – Use Positive Psychology to Reach Your Full Potential” by Martin E. P. Seligman. The intention of the analysis is to problematize the hegemonic discourse of positive psychology that is currently dominant. As a method, we use Michael Foucault’s discourse analysis, in the search to find out what emerges as dominant in relation to the problem in question. We realize that the discourse on happiness is constructed in a punctual, pragmatic and inductive manner. It always starts from a place of the individual subject, from individual experiences, to build a pattern of being, which aims to individualize behaviors according to the results demonstrated by the author and his psychological theory. From our analysis, we understand that the psychology founded in favor of this discourse of positivity works within a utilitarian ethics, and sometimes acts as a reproducer of hegemonic patterns of neoliberal society. Keywords: Speech; Happiness; Positive Psychology; Neoliberalism; Subjectivity.